Importance of Vertical Pathology of Debulking Specimens During Mohs Micrographic Surgery for Lentigo Maligna and Melanoma in Situ. Issue 3 (28th January 2013) - Iorizzo, Luciano J.; Chocron, Isaac; Lumbang, Wilfred; Stasko, Thomas
Abstract : Background: Recent Recovery Audit Contractor audits have targeted Mohs micrographic surgery (MMS) if permanent‐section pathology codes have been used on the same day. In lentigo maligna (LM) or melanoma in situ (MIS) cases, this is done to further evaluate the tumor for staging. Objective: To determine the percentage of LM, MIS, and thin invasive melanomas upstaged when a central debulking specimen from MMS is sent for permanent vertical sections. Methods: A single‐center retrospective study examining LM, MIS, and thin melanomas treated with MMS between January 1, 2004, and September 30, 2011, at Vanderbilt University was performed. The elements needed for staging, sex, age, tumor location, size, and previous skin cancer history were obtained. Results: Fourteen of 173 cases (8.1%; 95% confidence interval = 4.9–13.1%) were identified in which the tumor was upstaged; 13 of the cases initially diagnosed as LM or MIS were invasive (average Breslow depth 0.69 mm). One melanoma at 0.6 mm depth on initial biopsy increased to 1.2 mm after the debulking specimen from Mohs surgery was examined histologically. Debulking in four cases revealed a depth of 1 mm or greater. No differences existed in characteristics between upstaged and nonupstaged cases. Conclusion: When performing MMS for LM or MIS, it is appropriate and necessary to send the central debulking specimen for permanent histology for accurate tumor staging.